Sigma Convergence versus Beta Convergence: Evidence from U.S. County-Level Data - Andrew T. Young; Matthew J. Higgins; Daniel Levy (Journal of Money, Credit and Banking, 2008)
In this paper, we outline (i) why σ-convergence may not accompany β-convergence, (ii) discuss evidence of β-convergence in the United States, and (iii) use U.S. county-level data containing over 3,000 cross-sectional observations to demonstrate that σ-convergence cannot be detected at the county level across the United States, or within the large majority of the individual U.S. states considered separately. Indeed, in many cases statistically significant σ-divergence is found.
Keywords: O40; O11; O18; R11; 330; sigma-convergence; beta-convergence; Solow growth model; speed of convergence; balanced growth; U.S. county-level data; income distribution; Gini coefficient; income equality